Pemahaman Materi Pergaulan Bebas dan Akibatnya melalui Pelaksanaan Metode Moral Reasoning di SMA Muhammadiyah 1 Pekanbaru - Armaini; Gusma Afriani (Lembaga Anotero Scientific, 2021)
The purpose of this study was to determine the effect of the implementation of the moral reasoning method on the understanding of free association material and its consequences on Islamic religious education subjects at SMA Muhammadiyah 1 Pekanbaru. While the formulation of the problem is whether there is an effect of the implementation of the moral reasoning method on the understanding of free association material and its consequences on Islamic religious education subjects at SMA Muhammadiyah 1 Pekanbaru. This study uses two variables, namely: variable X (Influence of the Implementation of Moral Reasoning Method) and variable Y (Understanding Free Association Materials and Its Consequences). The data collection technique that the author uses is a questionnaire, test, observation and documentation technique. This study uses the serial correlation formula. The results of the study indicate that the effect of the implementation of the moral reasoning method has a significant influence on the understanding of promiscuity and its consequences. After analyzing the data, the authors conclude that the effect of the implementation of the Moral Reasoning Method on Islamic Religious Education Subjects is 89.47% or in the very good category. Meanwhile, the understanding of the material of promiscuity and its consequences is 92.08% or in the very good category. Through the serial correlation formula, the results of the study show that the correlation coefficient value of 0.710 is greater than the significant level of 1% 0.372 and 5% 0.288. This means that Ha is accepted and Ho is rejected. As a result, on Islamic Religious Education Subjects at SMA Muhammadiyah 1 Pekanbaru. Keywords: The Effect of Implementation of Moral Reasoning Method, Understanding of Free Association Materials and Its Effects.